Experimental results for structural design of Wire-and-Arc Additive Manufactured stainless steel members. (April 2020) - Laghi, Vittoria; Palermo, Michele; Gasparini, Giada; Girelli, Valentina Alena; Trombetti, Tomaso
Abstract: Additive Manufacturing has recently gained great importance to produce metallic structural elements for civil engineering applications. While a lot of research effort has been focused on different technologies (such as Powder Bed Fusion), there is still quite limited knowledge concerning the structural response of Wire-and-Arc Additive Manufactured (WAAM) metallic elements, as very few experimental campaigns aimed at assessing their geometrical and mechanical properties have been carried out. The paper presents selected results of a wide experimental campaign focused on the assessment of the main geometrical and mechanical properties of Wire-and-Arc Additive Manufactured (WAAM) stainless steel material, carried out at the Topography and Structural Engineering Labs of University of Bologna. In detail, the focus is on the characterization of the surface irregularities by means of various measuring techniques and on the evaluation of the main material mechanical properties, including tensile and compressive strengths, Young's modulus and post elastic behavior. Tests results have been interpreted through statistical tools in order to derive mean values and gather information about the variability of both geometrical and mechanical parameters. Highlights: An innovative manufacturing process among the metal 3D printing techniques for stainless steel material is first introduced in Structural Engineering field. For structural design purposes, the main issues in the realization of Wire-and-Arc Additive Manufactured stainless steel concern inherent geometrical imperfections to be properly characterized and the main material properties, influenced by the orientation of the elements. The first results of a wide experimental campaign devoted to assess the geometrical and mechanical characterization of Wire-and-Arc Additive Manufactured stainless steel elements evidence the need of proper evaluation of an effective geometry to derive the main mechanical parameters, which differ from the traditionally manufactured stainless steel material.